If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2 + 4 + -1x = -4 Reorder the terms: -2 + 4 + 3x + -1x = -4 Combine like terms: -2 + 4 = 2 2 + 3x + -1x = -4 Combine like terms: 3x + -1x = 2x 2 + 2x = -4 Solving 2 + 2x = -4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 2x = -4 + -2 Combine like terms: 2 + -2 = 0 0 + 2x = -4 + -2 2x = -4 + -2 Combine like terms: -4 + -2 = -6 2x = -6 Divide each side by '2'. x = -3 Simplifying x = -3
| 4d+3= | | 5m-2m-2=m-10 | | 6n-4=3n+11 | | 4x^2=-9+12x | | 2x-5=x+7-3x | | 6x+80+18x-40=180 | | 13-3n=1 | | 108=6-6(1-6x) | | 63=91-p | | 6x+80+18x-40=1 | | 49p^2+70p+25=0 | | 16-3h=4 | | 77x^4-x^2+49=0 | | 8u+17u+6u-16u+18u=18 | | 2x(3x-4)(5x+6)= | | 40x+2=8 | | 67+21=x | | 13t+9t+10=352 | | -3x+-6=18 | | 55=.20(285-10e) | | 20x+4=40 | | 16z+18z=18 | | 54r^2+72r+24=0 | | 15x-12x=141 | | -3(2y+1)=3-6y | | X*x*x=24 | | 7-4(2x+3)=3 | | 4(x-2)+3=35 | | x+8=-13+4x | | -(5y-9)=-4(y-7) | | 4t-t+3t+3t-8t=6 | | 8-3r=2 |